Awareness about human immunodeficiency virus/acquired immune deficiency syndrome and risk factors among out of school adolescents in an urban city - Bisht, Supriya; Prajapati, N C; Kumar, Rajesh; Agarwal, Renu (Indian Journal of Child Health, 2016)
Background: Adolescence is a complex phase of transition from childhood to adulthood. Present education programs usually overlook the needs of adolescents. Among those who are out of school, lack of appropriate level of education regarding human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS) make them more vulnerable. Objective: To find the awareness about HIV/AIDS and risk factor among out of school adolescents. Materials and Methods: In this cross-sectional observational study, 211 adolescentspresently not going to school for ?6 months were interviewed. A simple random sampling was done from different areas such as traffic signals, railway station, and slums. Results: Among studied adolescents, 25% had never been to school, while 44.6% had studied <5th class. Half of them worked outside while a quarter was involved in household work. About 44% of total adolescents had heard about HIV/AIDS with 16.3% from the age group 10-14 years and 63.2% from 15 to 19 years group. Awareness about sexual relationships was seen in 67% males and 51% females. Among those aware of physical relations, knowledge about condoms was present in 92% males and 82% females. Among sexually active adolescents (67), 74% males and 28% females were involved in physical relations outside marriage, comprising 38 (18%) of all interviewed, putting them at high-risk behavior. Around 25.8% males and none of the females among them had used condoms. 26 (68.4%) of these “at risk” adolescents had a relationship with consent, whereas 24 (63.2%) had multiple sexual partners. Conclusion: Being out of school, these adolescents have poor educational status. Their knowledge about HIV/AIDS is very poor. Adolescents with better education status, higher age and male gender were more aware regarding various aspects of HIV. Significant proportions among these indulge in high-risk sexual behavior, does not use condoms and have multiple sex partners. Their specific needs should be addressed by the ongoing campaigns and programs against HIV to spread more awareness.